Trismus during tracheal extubation as a complication of general anaesthesia – A case report - Radkowski Paweł; Kędziora Bartosz; Dawidowska-Fidrych Justyna (Open Medicine, 2022)
Tracheal extubation is a risky phase of anaesthesia. Most complications that occur when an endotracheal tube is removed are of minor nature, but those that require critical action can end in serious complications or even death. Patient – A 55-year-old woman was admitted for elective transabdominal hysterectomy and adnexal procedures. Anaesthesia – Standard monitoring. For induction, we used fentanyl, propofol, and rocuronium. The maintenance phase of anaesthesia was without complications. After extubation, the patient presented with severe trismus and mask ventilation was unsuccessful (cannot ventilate) – It was not until 200 mg of succinylcholine was administered that the masseter muscle spasm subsided.